An ultra-sensitive impedimetric immunosensor for detection of the serum oncomarker CA-125 in ovarian cancer patients1. Issue 8 (28th February 2015) - Johari-Ahar, M.; Rashidi, M. R.; Barar, J.; Aghaie, M.; Mohammadnejad, D.; Ramazani, A.; Karami, P.; Coukos, G.; Omidi, Y.
<x xml:space="preserve">Abstract</x> A gold electrode decorated with gold nanoparticles, CdSe quantum dots and anti-CA-125 antibody (MPA|AuNP@SiO2|QD|mAb immunosensor) sensitively specifically detects the CA-125 oncomarker.